2013
DOI: 10.1111/1365-2664.12087
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Managing urban ecosystems for goods and services

Abstract: Summary1. Concomitant with the rise in the proportion of the global human population that resides in urban areas has been growth in awareness of the importance of the provision of ecosystem goods and services to those people. Urban areas are themselves of significance in this regard because of their areal extent, and hence the quantity of services falling within their bounds, and because of the need for local provision of services to urban residents. 2. Here, we review key challenges to the effective managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
124
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 80 publications
1
124
0
3
Order By: Relevance
“…6) and evapotranspiration, indirectly reducing rainfall input and runoff. High-complexity habitat patches would be largely self-sustaining and internally maintained through the ecological interactions between vegetation, soils, litter and living organisms (Gaston et al, 2013). Therefore, a more pronounced ecological management of urban habitats that draws upon the natural ecosystem processes (McDonnell and Pickett, 1990) could result in substantial savings in terms of ongoing maintenance costs over both short and long term timespans.…”
Section: Implications For Urban Habitat Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…6) and evapotranspiration, indirectly reducing rainfall input and runoff. High-complexity habitat patches would be largely self-sustaining and internally maintained through the ecological interactions between vegetation, soils, litter and living organisms (Gaston et al, 2013). Therefore, a more pronounced ecological management of urban habitats that draws upon the natural ecosystem processes (McDonnell and Pickett, 1990) could result in substantial savings in terms of ongoing maintenance costs over both short and long term timespans.…”
Section: Implications For Urban Habitat Managementmentioning
confidence: 99%
“…Management practices (or lack of) can alter directly or indirectly each of these system components, determining changes in the overall complexity of urban habitats (Byrne, 2007;Gaston et al, 2013), and therefore directly impacting on the local hydrological processes (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial scale considered is also important. Looking across broad spatial scales, urban areas do indeed provide multiple ESs [4]. However, [ 2 _ T D $ D I F F ] these ES are supplied by areas of natural capital: urban parks, street trees, and private yards that are embedded within the urban matrix.…”
Section: Natural and Human-dominated Land Coversmentioning
confidence: 99%
“…Moreover, urban forests are subjected to human disturbance (e.g. pruning, irrigation, litter removal) and are manipulated with conflicting management goals (Gaston et al, 2013). Studies examining net effectiveness of urban forest maintenance practices are critical to the accurate evaluation and the development of appropriate forest management strategies aimed at mitigating climate change.…”
Section: Soil Respiration Management For Urban Forestmentioning
confidence: 99%
“…It is against the background of the swift growth of the urban population and the rapid expansion and regional densification of urban areas (United Nations, 2010), together with the need for better habitat and sustainable development, that the ecosystem services of green spaces are of increasing concern (Gaston et al, 2013). For example, recent research has demonstrated that urban areas are capable of storing much larger quantities of carbon than previously realized (Nowak and Crane, 2002;Scharenbroch, 2012;Nowak et al, 2013;Edmondson et al, 2014), which means they can make a greater contribution to greenhouse gas (GHG) mitigation.…”
Section: Introductionmentioning
confidence: 99%